Construction of three-dimensional/one-dimensional heterostructure of flower-like Sr nanoflowers on Se microrods decorated on reduced graphene oxide: an efficient electrocatalyst for oxidation of promethazine hydrochloride. (March 2022) - Hwa, K.Y.; Ganguly, A.; Santhan, A.; Sharma, T.S.K
Abstract: Three-dimensional (3D) strontium flowers were grown on well-defined one-dimensional (1D) selenium microrods using a simple hydrothermal technique at 180 °C. This resulted in the formation of a unique 3D/1D material which was ultrasonically treated with reduced graphene oxide to form a hybrid composite. The structural and functional analysis were performed using X-ray diffraction spectroscopy which rendered the material as pure and crystalline and Fourier transform infrared spectroscopy, respectively. X-ray photoelectron spectroscopy was performed to unravel the elemental composition and successful formation of the composite. Field emission scanning electron microscopy and transmission electron microscopy were performed to study the unique morphological features of the material. It was further used to fabricate a sensor for the detection of promethazine hydrochloride (PMZH) drug. The sensor showed a very low detection limit of 7.7 nM at a linear working range of 0.99 μM–900 μM and a sensitivity of 5.282 μA μM −1  cm −2 . The sensor showed an excellent analyte recovery rate for real-time analysis in biological and environmental samples. The results suggested that the sensor is effective for the detection of PMZH with feasibility for future commercialization. Highlights: Three-dimensional strontium flowers were grown on one-dimensional selenium microrods and were efficiently anchored with reduced graphene oxide. The availability of a large surface area facilitated rich interfacial electroactive sites for efficient detection of promethazine hydrochloride (PMZH). Sensitive detection of PMZH was possible with a lower limit of detection at 7.7 nM. The real-time applicability was successfully implied in biological, pharmaceutical, and environmental samples. Graphical abstract: Image 1